Physical characteristics and biological activities of thai flower extracts loaded in niosomes - Aranya Manosroi (2018)
The flower Bullet Wood (Mimusops elengi; ME), Cork Tree (Millingtonia hortensis; MH) and Cape Gardenia (Gardenia jasminoides; GJ) extracts prepared by supercritical carbon dioxide fluid extraction (ScCO 2 ) were loaded in niosomes [composed of Tween 61/cholesterol at 1:1 molar ratio] by the chloroform film method with sonication. The maximum loading concentration of all flower extracts in niosomes was 1% w/v. The niosomes both non-loaded and loaded with the flower extracts showed high physical stability with no change of color and precipitation when kept at various temperatures (4±2, 27±2 and 45±2°C) for 3 months. The ME extract loaded and non-loaded in niosomes exhibited the free radical scavenging (SC 50 ), metal chelating (MC 50 ) and lipid peroxidation inhibition (IPC 50 ) at 9.80±0.85, 32.15±0.34 and 16.69±7.35 mg/ml; 6.82±0.73, 0.46±0.09 and 0.45±0.02 mg/ml, respectively, while the metal chelating activity was not observed in the MH and GJ extracts. When loaded in niosomes, the cytotoxicity of all flower extracts on human skin fibroblast determined by the sulforhodamine B assay was decreased of 1.40-1.70 times. The ME extract loaded in niosomes exhibited higher active MMP-2 inhibition than the non-loaded extracts of 3.4 times. The niosomes loaded with all flower extracts especially the ME extract can be applied for the further development of the topical antiaging products.